2019
DOI: 10.1016/j.ynpai.2019.100027
|View full text |Cite
|
Sign up to set email alerts
|

Methanol extract of Cola nitida ameliorates inflammation and nociception in experimental animals

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…255 Phytochemical quantification of methanol extract of C. nitida revealed the presence of alkaloids, anthraquinones, cardiac glycosides, flavonoids, steroids, tannins, and terpenoids. 256,257…”
Section: Indigenous Nigerian Medicinal Plants Whose Bioactive Compoun...mentioning
confidence: 99%
“…255 Phytochemical quantification of methanol extract of C. nitida revealed the presence of alkaloids, anthraquinones, cardiac glycosides, flavonoids, steroids, tannins, and terpenoids. 256,257…”
Section: Indigenous Nigerian Medicinal Plants Whose Bioactive Compoun...mentioning
confidence: 99%
“…Phytochemical profiling of C. nitida showed several secondary metabolites. The nuts from C. nitida revealed the presence of various chemical compounds, including catechin, caffeine, epicatechin, procyanidin B1, procyanidin B2, polyphenols, alkaloids, tannins, saponins, bromelain, cardenolides, proanthocyanidins, triterpenes, glycosides, flavonoids, anthraquinones, steroids (Adedayo et al, 2019;Daels-Rakotoarison et al, 2003;Dah-Nouvlessounon et al, 2015;Ganiyu et al, 2014;Momo et al, 2009;Niemenak et al, 2008;Sonibare et al, 2009). Bark from C. nitida contains tanins, saponosides, anthocyanins, flavonoids, glycosides, alkaloids, and polyphenols (Dah-Nouvlessounon et al, 2015;Dawole et al, 2013;Eddy, 2010) (Figure 2 andTable 4).…”
Section: Phytochemistrymentioning
confidence: 99%
“…Several recent studies have demonstrated that the lipid peroxidation generated by iron in the rat pancreas can be inhibited by Cola nitida extract in a dose-dependent manner (Ganiyu et al, 2014), and that the extract also has high DPPH radical scavenging activity (EC 50 = 2. 2 mg/mL) (Adedayo et al, 2019).…”
Section: An Oxidant Ac VI Esmentioning
confidence: 99%
“…Non-steroidal anti-inflammatory drugs (NSAIDs) as the most common drugs used to manage pain and inflammation elicit analgesic and antiiinflammatory action by inhibiting cyclooxygenase (COX) enzyme, which interferes with PG synthesis (Adedayo et al 2019). The opioids have also been employed to manage severe pain.…”
Section: Introductionmentioning
confidence: 99%
“…Some important analgesic agents, such as acetylsalicylic acid and morphine, were sourced from medicinal plants (Abubakar et al 2020). Therefore, there is increasing interest in developing effective anti-inflammatory and analgesic drugs from herbal preparations in managing pain and inflammation (Adedayo et al 2019).…”
Section: Introductionmentioning
confidence: 99%